Galactorrhea after Breast Augmentation with Mastopexy: Case Reports and Literature Review - Payer, Juraj; Patzelt, Matej; Kralik, Roman; Makel, Michal (Archives of Plastic Surgery, 2025)
Galactorrhea is a rare but well-described complication following aesthetic breast surgery. Augmentation with mastopexy is a procedure that combines breast tissue reduction with volume augmentation; however, only few cases of galactorrhea were described following this procedure. This report concerns three cases of galactorrhea after augmentation with mastopexy provided by two surgeons (J.P. and M.P.). Patients did not report any significant gynecological history, including a history of oral hormonal intake or galactorrhea in the past. All three patients underwent the dual plane breast augmentation together with the Wise-pattern breast lift. In two cases, the first symptoms occurred in the second week, and in one case in the third week after surgery, manifesting as breast pain and swelling. These clinical issues, accompanied by a small amount of white fluid secretion from the vertical scar, scar around nipple-areolar complex, and from the T-junction, were presented to the operating surgeons. Galactorrhea came to consideration after a negative microbiological examination. In two cases, galactorrhea was treated with oral dopaminergic medication cabergoline, with a good response to the therapy. All symptoms, including redness and pain, fully resolved at the 21st postoperative day without the necessity of surgical revision.One patient with bilateral secretion was treated by early operative revision. In the following days, secretion ceased, and after drain removal, further complications did not occur. Aesthetic results after 12 months were satisfactory in all patients.In conclusion, galactorrhea is a rare but significant complication of any mammaplasty surgery. Untreated secretion may lead to severe complications; however, early recognition and treatment may lead to good results and patient satisfaction.
Keywords: galactorrhea; breast augmentation with mastopexy; case report